Caribbean Community for all - Bourne, Compton (CDB St. MichaelBB, 2003)
Describes the nature and evolution of the Caribbean Community. Looks at economic heterogeneity and similarity. Comments on intra-community trade and labour in the Community. Focuses on financial capital in the Community and non market factors.